2022
DOI: 10.31234/osf.io/y5h78
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning where to be flexible: Using environmental cues to regulate cognitive control

Abstract: Cognitive flexibility refers to a mental state that allows efficient switching between tasks. While deciding to be flexible is often ascribed to a strategic resource-intensive executive process, people may also simply use their environment to trigger different states of mental flexibility. We developed a paradigm where participants were exposed to two environments with different task switching probabilities, followed by a probe phase to test the impact of environmental cues. Our results show that people were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, the authors' findings may not be directly comparable to the current results since Ileri-Tayar et al (2022) were interested in persisting conflict adaptation to mostly congruent or mostly incongruent stimuli or stimulus features in neutral transfer lists, while the current study probed flexibility adaptations to list-wide context. Additionally, also investigating contextual adaptations of flexibility, a recent study found that participants adapted to task-irrelevant environmental cues that signal varying demands for switching, although the authors did not test for cross-task transfer (Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors' findings may not be directly comparable to the current results since Ileri-Tayar et al (2022) were interested in persisting conflict adaptation to mostly congruent or mostly incongruent stimuli or stimulus features in neutral transfer lists, while the current study probed flexibility adaptations to list-wide context. Additionally, also investigating contextual adaptations of flexibility, a recent study found that participants adapted to task-irrelevant environmental cues that signal varying demands for switching, although the authors did not test for cross-task transfer (Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The number of learning trials ranged from 192 to 320. This may simply not be enough time to form a sufficiently strong cue–transition association (see Xu et al, 2023). Notably, with the current procedure, learning can continue into the first part of the test phase where the cues are still predicting the upcoming transition in forced-choice trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, sometimes it is more beneficial to focus on a single task, and we should apply a less flexible, but more stable cognitive strategy, e.g., to better shield from interfering information. This regulation of the trade-off between cognitive flexibility and cognitive stability is important, as both control modes guide adaptive behaviour depending on the context (Braem & Egner, 2018;Brosowsky & Egner, 2021;Cohen et al, 2007;Diamond, 2013;Egner, 2023;Goschke & Bolte, 2014;Xu et al, 2023). In this study, we aimed to test if people learn to be more flexible (stable) when cognitive flexibility (stability) is selectively reinforced.…”
Section: Introductionmentioning
confidence: 99%